The element of crime [videorecording (DVD)] - Trier, Lars von, 1956-; Elphick, Michael, 1946-2002; Knight, Esmond, 1906-1987; Lai, Me Me (Criterion collection, 2000)
The story of an exiled ex-cop who returns to his old beat to catch a serial killer preying on young girls.